Mesozoic dinosaurs from Brazil and their biogeographic implications - Bittencourt,Jonathas S. (2011)
The record of dinosaur body-fossils in the Brazilian Mesozoic is restricted to the Triassic of Rio Grande do Sul and Cretaceous of various parts of the country. This includes 21 named species, two of which were regarded as nomina dubia, and 19 consensually assigned to Dinosauria. Additional eight supraspecific taxa have been identified based on fragmentary specimens and numerous dinosaur footprints known in Brazil. In fact, most Brazilian specimens related to dinosaurs are composed of isolated teeth and vertebrae. Despite the increase of fieldwork during the last decade, there are still no dinosaur body-fossils of Jurassic age and the evidence of ornithischians in Brazil is very limited. Dinosaur faunas from this country are generally correlated with those from other parts of Gondwana throughout the Mesozoic. During the Late Triassic, there is a close correspondence to Argentina and other south-Pangaea areas. Mid-Cretaceous faunas of northeastern Brazil resemble those of coeval deposits of North Africa and Argentina. Southern hemisphere spinosaurids are restricted to Africa and Brazil, whereas abelisaurids are still unknown in the Early Cretaceous of the latter. Late Cretaceous dinosaur assemblages of south-central Brazil are endemic only to genus or, more conspicuously, to species level, sharing closely related taxa with Argentina, Madagascar, Indo-Pakistan and, to a lesser degree, continental Africa.